2003
DOI: 10.5713/ajas.2003.445
|View full text |Cite
|
Sign up to set email alerts
|

Essentiality of Histidine in Ruminant and Other Animals Including Human Beings

Abstract: Concept and establishment of essential amino acids in animals and human beings rendered immeasurable contributions to animal production and human health. In ruminant animals, however, essential amino acids have never been completely established. The present review proposes a hypothesis that histidine may not be an essential amino acid for normal growing cattle (Japanese black) at least at the growing stage after about 450 kg of body weight on the basis of the experimental results of histidinol dehydrogenase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Taking into account these other parameters of protein metabolism, histidine is considered as an indispensable AA in healthy adults. Some studies have also reported the indispensability of histidine for ruminants [4]. Histidine is abundant in red meat and fish, but its content varies among fish species, from histidine-rich fish (dark muscle fish) to histidine-poor fish (white muscle fish).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account these other parameters of protein metabolism, histidine is considered as an indispensable AA in healthy adults. Some studies have also reported the indispensability of histidine for ruminants [4]. Histidine is abundant in red meat and fish, but its content varies among fish species, from histidine-rich fish (dark muscle fish) to histidine-poor fish (white muscle fish).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are indications that histidinol dehydrogenase, the enzyme that catalyzes the terminal step in the biosynthesis of His, is expressed in the liver and kidney but not in the muscle of pigs (Onodera, 2003). In humans, the essentiality of His in healthy adults has been a controversial topic because His is not required to maintain the nitrogen equilibrium (Rose et al, 1951).…”
Section: Gloaguen Le Floc'h Primot Corrent and Van Milgenmentioning
confidence: 99%
“…The FEEDAP Panel notes that histidine is different from other essential amino acids in that substantial quantities exist in haemoglobin and in the form of free imidazol derivatives (dipeptides) in animal muscle tissues such as carnosine (b-alanyl histidine), anserine (b-alanyl-1-methyl histidine) and balenine (b-alanyl-3-methyl histidine) leading to the difficulty of establishing conclusive indispensability. Furthermore, these dipeptides have anti-inflammatory and antioxidant effects; it is believed that they interact with oxygen radicals and lipid peroxidation products to prevent membrane damage (Buttery and D'Mello, 1994;Onodera, 2003).…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%